PENGARUH FAKTOR EKSTERNAL TERHADAP HARGA SAHAM PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2019)
This study aims to examine how much "the influence of external factors on stock prices in banks listed on the Indonesia Stock Exchange". In this study the sample taken was a banking company listed on the Indonesia Stock Exchange in the period 2016-2018. Data analysis method used in this study is to use multiple regression analysis. The results of the study indicate that inflation, interest rates and exchange rates have no significant effect on the price of banking shares listed on the Indonesia Stock Exchange. The most dominant variable in this study is inflation which has a positive and not significant effect on the price of banking shares listed on the Indonesia Stock Exchange. It is hoped that this research can be used as a work in adding insight to knowledge that can further broaden the mindset of readers, especially regarding the influence of external factors on the Banking Stock Prices listed on the Indonesia Stock Exchange.